The suitability of P. falciparum merozoite surface proteins 1 and 2 as genetic markers for in vivo drug trials in Yemen. - Nazeh M Al-abd; Mohammed A K Mahdy; Abdulsalam M Q Al-Mekhlafi; Georges Snounou; Nazia B Abdul-Majid; Hesham M Al-Mekhlafi; Mun Y Fong (PLoS ONE, 2013)
BACKGROUND: The accuracy of the conclusions from in vivo efficacy anti-malarial drug trials depends on distinguishing between recrudescences and re-infections which is accomplished by genotyping genes coding P. falciparum merozoite surface 1 (MSP1) and MSP2. However, the reliability of the PCR analysis depends on the genetic markers' allelic diversity and variant frequency. In this study the genetic diversity of the genes coding for MSP1 and MSP2 was obtained for P. falciparum parasites circulating in Yemen. METHODS: Blood samples were collected from 511 patients with fever and screened for malaria parasites using Giemsa-stained blood films. A total 74 samples were infected with P. falciparum, and the genetic diversity was assessed by nested PCR targeting Pfmsp1 (Block2) and Pfmsp2 (block 3). RESULTS: Overall, 58%, 28% and 54% of the isolates harboured parasites of the Pfmsp1 K1, MAD20 and RO33 allelic families, and 55% and 89% harboured those of the Pfmsp2 FC27 and 3D7 allelic families, respectively. For both genetic makers, the multiplicity of the infection (MOI) was significantly higher in the isolates from the foothills/coastland areas as compared to those from the highland (P<0.05). Pfmsp2 had higher number of distinct allelic variants than Pfmsp1 (20 vs 11). The expected heterozygosity (HE) for Pfmsp1 and Pfmsp2 were 0.82 and 0.94, respectively. Nonetheless, a bias in the frequency distribution of the Pfmsp1 allelic variants was noted from all areas, and of those of Pfmsp2 in the samples collected from the highland areas. CONCLUSIONS: Significant differences in the complexity and allelic diversity of Pfmsp1 and Pfmsp2 genes between areas probably reflect differences in the intensity of malaria transmission. The biased distribution of allelic variants suggests that in Yemen Pfmsp1 should not be used for PCR correction of in vivo clinical trials outcomes, and that caution should be exercised when employing Pfmsp2.